Effects of transgenic expression of dopamine beta hydroxylase (Dbh) gene on blood pressure in spontaneously hypertensive rats - Pravenec, M; Landa, V; Zídek, V; Mlejnek, P; Šilhavý, J; Mir, S A; Vaingankar, S M; Wang, J; Kurtz, T W (Physiological research, 2016)
The spontaneously hypertensive rat (SHR) is the most widely used animal model of essential hypertension and left ventricular hypertrophy. Catecholamines play an important role in the pathogenesis of both essential hypertension in humans and in the SHR. Recently, we obtained evidence that the SHR harbors a variant in the gene for dopamine beta hydroxylase (Dbh) that is associated with reduced adrenal expression of Dbh mRNA and reduced DBH enzymatic activity which correlated negatively with blood pressure. In the current study, we used a transgenic experiment to test the hypothesis that reduced Dbh expression predisposes the SHR to hypertension and that augmentation of Dbh expression would reduce blood pressure. We derived 2 new transgenic SHR-Dbh lines expressing Dbh cDNA under control of the Brown Norway (BN) wild type promoter. We found modestly increased adrenal expression of Dbh in transgenic rats versus SHR non-transgenic controls that was associated with reduced adrenal levels of dopamine and increased plasma levels of norepinephrine and epinephrine. The observed changes in catecholamine metabolism were associated with increased blood pressure and left ventricular mass in both transgenic lines. We did not observe any consistent changes in brainstem levels of catecholamines or of mRNA levels of Dbh in the transgenic strains. Contrary to our initial expections, these findings are consistent with the possibility that genetically determined decreases in adrenal expression and activity of DBH do not represent primary determinants of increased blood pressure in the SHR model.
Keywords: Brain Stem; dopamin; Rats; regulace genové exprese enzymů; Dopamine beta-Hydroxylase; DNA, Complementary; krevní tlak; Hypertension; Transgenes; transgeny; potkani inbrední SHR; nadledviny; Animals, Genetically Modified; noradrenalin; krysa rodu Rattus; komplementární DNA; zvířata; adrenalin; Blood Pressure; Rats, Inbred BN; geneticky modifikovaná zvířata; mozkový kmen; potkani inbrední BN; Adrenal Glands; Dopamine; Gene Expression Regulation, Enzymologic; hypertenze; Norepinephrine; Rats, Inbred SHR; Epinephrine; dopamin-beta-hydroxylasa; Animals